Losartan, but not Enalapril and Valsartan, Inhibits the Expression of IFN-γ, IL-6, IL-17F and IL-22 in PBMCs from Rheumatoid Arthritis Patients - Cardoso, Pablo R. G. (Open Rheumatol J, 2018)
BACKGROUND: Rheumatoid Arthritis (RA) is a chronic and inflammatory disease that affects about 1% of the world's population. Almost 70% of RA patients have a cardiovascular disease such as Systemic Arterial Hypertension (SAH). Inflammatory cytokines are clearly involved in the pathogenesis of RA and correlated with SAH. OBJECTIVE: It is necessary to understand whether the antihypertensive drugs have a dual effect as immunomodulators and which one is the best choice for RA SAH patients. METHODS: Peripheral Blood Mononuclear Cells (PBMCs) from 16 RA patients were purified and stimulated or not stimulated with anti-CD3 and anti-CD28 mAB and were treated with Enalapril, Losartan and Valsartan at 100μM. Patients were evaluated for clinical and laboratory variables including measures of disease activity by Clinical Disease Activity Index (CDAI) and Disease Activity Score (DAS28). Cytokines were quantified by ELISA sandwich. RESULTS: Losartan was able to reduce levels of IFN-γ (p = 0.0181), IL-6 (p = 0.0056), IL-17F (0.0046) and IL-22 (p = 0.0234) in RA patients. In addition, patients in remission and mild score (DAS28<3.2 and CDAI<10) had a better response to treatment. On the other hand, patients in moderate and severe activity had poor response to Losartan in cytokine inhibition. CONCLUSION: PBMCs from RA patients are responsive in inhibiting proinflammatory cytokines using Losartan better than Enalapril and Valsartan and it could be a better antihypertensive choice for patients with RA and systemic arterial hypertension treatment.